Evidence and role of phlebitis and lipid infiltration in the onset and pathogenesis of Wooden Breast Disease in modern broiler chickens. Issue 6 (2nd November 2017) - Papah, Michael B.; Brannick, Erin M.; Schmidt, Carl J.; Abasht, Behnam
ABSTRACT: Wooden Breast Disease (WBD), a myopathy that frequently affects modern broiler chickens, is a disorder that has been associated with significant economic losses in the poultry industry. To examine tissue changes associated with the onset and early pathogenesis of this disorder, a time-series experiment was conducted using chickens from a high-breast-muscle-yield, purebred commercial broiler line. Birds were raised for up to seven weeks, with a subset of birds sampled weekly. Breast muscle tissues were extracted at necropsy and processed for analysis by light microscopy and transmission electron microscopy. Histologic presentation indicated localized phlebitis with lipogranulomas in Week 1, focal single-myofibril degeneration in Week 2 preceding an inflammatory response that started in Week 3. Lesions in Week 4 were characterized by multifocal to diffuse muscle fibre degeneration, necrosis, interstitial oedema accompanied by increased lipid and inflammatory cell infiltration. Lesions in Weeks 5–7 revealed diffuse muscle degeneration, necrosis, fibrosis and fatty infiltration with lipogranulomas. Ultrastructural examination showed myofibrillar splitting and degeneration, irregular, displaced and degenerated Z-lines, mitochondrial degeneration and interstitial fibrosis with dense regular collagen fibres. This study, therefore, demonstrates that WBD exhibits an earlier onset in modern broilers than when detectable by clinical examination. Further, this study shows that the disease assumes a progressive course with acute vasculitis, lipid deposition and myodegeneration occurring in the earlier stages, followed by a chronic fibrotic phase.